Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/ijmm.2016.2754
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-33b suppresses the proliferation and metastasis of hepatocellular carcinoma cells through the inhibition of Sal-like protein 4 expression

Abstract: MicroRNAs (miRNAs or miRs) have been found to participate in the development and malignant progression of human cancers by negatively mediating the expression of their target genes. Recently, miR‑33b has been reported to be involved in multiple types of human cancer, including hepatocellular carcinoma (HCC). However, the underlying regulatory mechanisms of miR‑33b in HCC cell growth and metastasis remain largely unclear. In the present study, RT-qPCR revealed that miR‑33b was significantly downregulated in HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Our study also demonstrated that miR-33b could suppress various cellular processes such as invasion, migration, proliferation, EMT, and tumor growth of GBC through down-regulating the expression of CROCC. In consistency with our study, Wu et al also observed that the overexpression of miR-33b suppressed the proliferation, migration, and invasion of hepatocellular carcinoma cells [30]. Also, an enforced expression of miR-33b resulted in its inhibitory effects on EMT in lung cancer cells [31].…”
Section: Discussionsupporting
confidence: 92%
“…Our study also demonstrated that miR-33b could suppress various cellular processes such as invasion, migration, proliferation, EMT, and tumor growth of GBC through down-regulating the expression of CROCC. In consistency with our study, Wu et al also observed that the overexpression of miR-33b suppressed the proliferation, migration, and invasion of hepatocellular carcinoma cells [30]. Also, an enforced expression of miR-33b resulted in its inhibitory effects on EMT in lung cancer cells [31].…”
Section: Discussionsupporting
confidence: 92%
“…[42] hsa-miR-33b-5p was shown to constrain tumor cell growth and induce cell cycle arrest, and decreased expression level in liver cancer and CRC, which is inconformity with the results of this paper. [43,44] However, there is a study that show high expression of miR-33b in lung cancer. [45] SLCO1B3 gene encodes organic anion transporting polypeptide 1B3 (OATP1B3).…”
Section: Discussionmentioning
confidence: 99%
“…In China, gastric cancer is the third most common cause of cancer-associated mortality ( 18 ). In the year 2002, the age standardized incidence rate was 22.0/100,000 males and 10.4/100,000 females and the mortality rate was 16.3/100,000 males and 7.9/100,000 females, according to the global estimation-GLOBOCAN 2002 ( 19 ). The property of easy distant metastasis makes current therapeutics unable to treat gastric cancer in all patients.…”
Section: Discussionmentioning
confidence: 99%